2022
DOI: 10.1186/s12885-022-09887-5
|View full text |Cite
|
Sign up to set email alerts
|

HE4 as a serum biomarker for the diagnosis of pelvic masses: a prospective, multicenter study in 965 patients

Abstract: Background To evaluate the diagnostic value of adding human epididymis protein 4 (HE4), cancer antigen 125 (CA125) and risk of malignancy algorithm (ROMA) to ultrasound for detecting ovarian cancer in patients with a pelvic mass. Methods This was a prospective, observational, multicenter study. Patients aged > 18 years who were scheduled to undergo surgery for a suspicious pelvic mass had CA125 and HE4 levels measured prior to surgery, in additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In addition, Dochez V. et al [26], who studied the usefulness of CA125, HE4, ROMA, and RMI tests in the diagnosis of ovarian cancer, showed that the most effective diagnostic method to date is the simultaneous determination of CA125 and HE4 [26]. Braicu EI et al [27] discovered that CA125, HE4, and ROMA exhibit markedly improved diagnostic performance in advanced ovarian cancer (AUC > 0.92) compared to early stage. The researchers found that in the differentiation between OC and endometriosis, both the ROMA (SN 99%) and HE4 (SN 98.1%) performed superiorly compared to CA125 (SN 75.0%) with a specificity rate of 75.4% [27].…”
Section: Ca125 and Its Combinations With Other Parameters; Algorithms...mentioning
confidence: 99%
“…In addition, Dochez V. et al [26], who studied the usefulness of CA125, HE4, ROMA, and RMI tests in the diagnosis of ovarian cancer, showed that the most effective diagnostic method to date is the simultaneous determination of CA125 and HE4 [26]. Braicu EI et al [27] discovered that CA125, HE4, and ROMA exhibit markedly improved diagnostic performance in advanced ovarian cancer (AUC > 0.92) compared to early stage. The researchers found that in the differentiation between OC and endometriosis, both the ROMA (SN 99%) and HE4 (SN 98.1%) performed superiorly compared to CA125 (SN 75.0%) with a specificity rate of 75.4% [27].…”
Section: Ca125 and Its Combinations With Other Parameters; Algorithms...mentioning
confidence: 99%
“…Currently, the most commonly used tumor marker for OC screening in clinical practice is Carbohydrate Antigen 125 (CA125) [ 21 ] and Human Epididymis Protein 4 (HE4) [ 22 ]. Given that other benign diseases can also cause elevated serum biomarkers, the diagnostic specificity and sensitivity of using serum CA125 or HE4 alone are not high [ 23 ]. Existing studies have attempted to establish prognostic models for patients with OC based on clinicopathologic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have attempted to establish prognostic models for patients with OC based on clinicopathologic characteristics. For instance, the Risk of Ovarian Malignancy Algorithm (ROMA) model incorporated both serum CA125 and HE4, nevertheless, the model did not fully address the challenge of detecting OC with high risk [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…WFDC2 is a well-established ovarian cancer biomarker (AlSomairi et al, 2024;Braicu et al, 2022;Utkarsh et al, 2023) and is also associated with HGSC patient survival (James et al, 2022). PPIB was selected as a control gene, and it is already used in several ovarian cancer studies by RNAscope assay and RT-PCR analysis (Desbois et al, 2020;Pan & Ma, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…CCNE1 amplification, occurring in 15-20% of HGSC cases (Bell et al, 2011; Jamalzadeh et al, 2022; Marone et al, 1998), has been linked to HGSC patient survival (Chan et al, 2020; Jamalzadeh et al, 2022; Stronach et al, 2018). WFDC2 is a well-established ovarian cancer biomarker (AlSomairi et al, 2024; Braicu et al, 2022; Utkarsh et al, 2023) and is also associated with HGSC patient survival (James et al, 2022). PPIB was selected as a control gene, and it is already used in several ovarian cancer studies by RNAscope assay and RT-PCR analysis (Desbois et al, 2020; Pan & Ma, 2020).…”
Section: Introductionmentioning
confidence: 99%